The Role of Influencers in Indonesia’s “17+8 Tuntutan Rakyat” Movement: A Critical Discourse Analysis - Arum Puspaningtyas (Universitas Airlangga, 2026)
The “17+8 Tuntutan Rakyat” movement that emerged in August 2025 became a significantphenomenon in the development of digital democracy in Indonesia through the role of influen-cers on Instagram. The movement reflects the political awareness of Millennials and GenerationZ in expressing criticism toward the state within digital public spaces. This study aims to describethe representation of people’s struggle, power relations, and social influence constructed in in-fluencers’ Instagram posts using Norman Fairclough’s (1995) three-dimensional Critical Discour-se Analysis (CDA) framework. This research employed a descriptive qualitative method usingdata from influencers’ Instagram posts containing texts, hashtags, and visual symbols related tothe “17+8 People’s Demands” movement. The analysis focused on textual, discursive, and socio-cultural dimensions, supported by Austin’s speech act theory and Bourdieu’s theory of symboliccapital. The findings reveal that locutionary, illocutionary, and perlocutionary acts were used topresent facts, direct collective action, and generate audience participation. Hashtags, personaldeixis, and concise phrases strengthened solidarity. Influencers also functioned as discourse ini-tiators who bridged structural state issues with popular digital language. This study contributes tothe field of critical discourse studies by offering an empirically grounded framework for analyzinginfluencer-mediated political discourse, providing scholars and practitioners with deeper insightsinto how digital language strategies function as tools of civic mobilization in the context of con-temporary Indonesian democracy.